Sistem Pendukung Keputusan Dalam Menentukan Kinerja Aparatur Desa Pada Kecamatan Pugung Menggunakan Metode SAW - Tri Susilowati; Urip Indrajaya; Wulandari - (Jurnal Sistem Informasi, 2017)
AbstractThe need for a strong personnel resources facing the village of institutional change is not only driven by internal factors but also external factors. Internal factors because when village officials should have the skills and knowledge such as making regulations parley villages along the body of the village, the village financial management, and others. The demands of rural communities will be their satisfactory services is something that must immediately responded village government. The results can be concluded from this study that the village government performance in providing services must be assessed due to the creation of good governance (good governance). With their performance appraisal is expected to cause a sense of morale officers Pugung village in the district, so it will be offset by good discipline as well. This decision support system designed to determine the performance of the apparatus Pugung villages in the district. The author in this study using SAW. With the decision support system is very useful in improving the performance of the apparatus Pugung village in the district, and as motivation village officials in providing services to the public. The results of this study best performance was obtained on behalf of Edi Setiawan from Sinar Agung village with a value of 0.92.Keywords: SPK, performance, village officials, Simple Additive Weighting (SAW)